Effects of ultrasonic cleansing on oily facial skin: a Review of the Literature - Sabilo, Karolina; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2024)
Abstract. People of all ages suffer from persistently discoloured facial skin with rashes and acne. Regular skin care, cosmetic products and skin cleansing procedures are important to tackle this problem. One of the potentials, non-traumatic skin cleansing treatments for oily facial skin is ultrasound. Objective. To analyse from a theoretical point of view the problem of oily facial skin and the effects of ultrasonic cleansing on the skin. Methods. A review of research articles using the keywords: oily skin, skin problems, ultrasonic facial cleansing, skin cleansing, and their combinations with the words "and", "or". The search for research articles was conducted in PubMed, Google Scholar, BMJ, Clin Dermatol electronic database. The literature review included 22 open-access and full-length articles on the topic, written in English, from 2016 to 2022. Results of the literature review. This article covers the main problems of oily facial skin, the effects of external and internal factors on the skin, the effects of ultrasonic cleansing on oily facial skin, and the use of preventive measures to maintain a healthy pH balance in oily facial skin. Conclusion. 1. Oily facial skin is caused by hormonal disorders that stimulate the production of sebum, making the skin prone to shine, oiliness, rashes and clogged pores. Exogenous exposure sensitises the skin. Maintaining a healthy skin balance is important for a daily facial skin routine. 2. The ultrasound waves, tailored to the permeability of the facial skin to electrical currents, have a positive effect on oily facial skin, adding active ingredients to the deepest layers of the skin, improving elasticity and hydration, and lowering sebum levels.